Procurement Ethics and Contract Performance in Local Governments: A Case Study of Mbale District Local Government - Kadde Richard (Uganda Christian University, 2024)
This research aims to investigate the impact of procurement ethics on contract performance within the Mbale District Local Government. Procurement ethics, encompassing principles such as transparency, confidentiality, and accountability, are crucial for ensuring effective and equitable public procurement processes. This study will analyze how ethical practices influence the execution and outcomes of contracts in the Mbale District, a region characterized by significant public-sector procurement activities for example rehabilitation of boreholes, construction of school pit latrines and many others. By examining procurement processes and their adherence to ethical standards, the research seeks to highlight the correlation between ethical behavior and contract performance metrics, such as timeliness, cost-effectiveness, and quality. The research will employ a mixed-methods approach, combining quantitative data from procurement performance reports with qualitative insights from interviews and surveys of key stakeholders, including procurement officers, CAO, District Information Officer, assistant CAO, Human Resource Officer, Records Officer, CDO, Production Officer, Finance Officer, Health Officer, District Engineer and Education Officer, and secretary service commission and other stakeholders in contract management. This methodology enabled a comprehensive assessment of how variations in ethical practices impact contract execution and overall performance. The study also explored specific ethical challenges encountered in the district, such as corruption or favoritism, and their implications for procurement outcomes. By identifying these challenges, the research aims to provide actionable recommendations for enhancing procurement ethics and improving contract performance. Ultimately, the findings of this research contributed to the broader understanding of how ethical procurement practices affect public sector efficiency and effectiveness. The insights gained could inform policy reforms and best practices not only within Mbale District but also in other similar contexts. By fostering a culture of ethical procurement, local governments can better ensure that public resources are utilized efficiently and that contracts are performed to the highest standards, thereby improving service delivery and accountability in public administration.